Empowerment of Fishermen Communities through the Utilization of Spinning Machine Technology in Weru Village, Paciran District: Pemberdayaan Masyarakat Nelayan Melalui Pemanfaatan Teknologi Mesin Pemintal Tali Tampar di Desa Weru Kecamatan Paciran - Mario Sariski Dwi Ellianto; Yusuf Eko Nurcahyo; Fajrul Fikri Al Firdausi (Jurnal Soeropati, 2022)
The problem faced by the Slap Strap Making Business Group is that the process of making slap ropes is still manual using a hand drill. This business group experienced many problems when using manual methods, such as the results of the twisting of the slapping rope were not uniform and many were loose. The second obstacle faced is that manual labor requires a lot of manpower for the slap rope spinning process. The last obstacle faced is when using a spinning machine there is a concern that the electricity supply will not be able to meet because the electricity supply in the area around the coast still uses 450 watts of electricity. So that if you use a spinning machine, it is hoped that the machine can be energy efficient and easy to use. The right solution is offered to solve the problem of the need for a spinning machine that is energy efficient and easy to use, namely the manufacture of a slap rope spinning machine with a chain shaft system. The machine includes various components, among others; frames, shafts, bearings, gears, dimmers, belts and pulleys. The propulsion system uses an electric motor. By using the slap rope spinning machine, it is be able to increase the efficiency and effectiveness of the slap rope spinning process.